SISTEM OPERASIONAL UNIT PELAYANAN TERPADU SATU ATAP ( UPTSA ) SEBAGAI MODAL PELAYANAN SIPIL DINAS PERIZINAN PEMERINTAH KOTA YOGYAKARTA - Wicaksono, Baskoro (Universitas Riau, 2014)
Prima Public Services are services that are under one roof agencies. In Yogyakarta, one-stopservice is realized in the form of the establishment of the ?Dinas Perizinan?, formerly known asOne-Stop Integrated Service Unit (UPTSA). The existence of this new service brings change inThe pattern of service so that it gets a good response from the public. This research wasconducted in Yogyakarta is First, How the production and distribution of